2003
DOI: 10.1111/j.1745-4530.2003.tb00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical Changes During Coffee Roasting in Rotary Conduction‐type Heating Units

Abstract: Coffee beans were roasted in a rotary conduction‐type‐heating unit under constant heating surface or product temperatures ranging from 200 to 240C or 170 to 210C, respectively. the roasting duration was varied from 0 to 70 min through intermittent sampling of coffee beans at selected intervals. There were marked changes in physical conditions of coffee beans during roasting. the specific gravity, bulk density, susceptibility to breakage, and color lightness index L changed from 1.2 to 0.5, 0.7 to 0.3 g/cm3, 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 5 publications
1
11
0
2
Order By: Relevance
“…This effect was previously observed in several studies on coffee (Illy & Viani, 1995;Singh et al, 1997;Mwithiga & Jindal, 2003;Mendonça et al, 2009;Vargas-Elías, 2011 roasting results in greater weight loss and increased coffee volume and, therefore, lower ρ ap . The change in volume is related to the increase in internal cell pressure that occurs during heat transfer and in pyrolysis reactions, which are more intense during longer roasts (Borges et al, 2004).…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…This effect was previously observed in several studies on coffee (Illy & Viani, 1995;Singh et al, 1997;Mwithiga & Jindal, 2003;Mendonça et al, 2009;Vargas-Elías, 2011 roasting results in greater weight loss and increased coffee volume and, therefore, lower ρ ap . The change in volume is related to the increase in internal cell pressure that occurs during heat transfer and in pyrolysis reactions, which are more intense during longer roasts (Borges et al, 2004).…”
Section: Resultssupporting
confidence: 49%
“…Roast level has been reported to determine the final quality of the beverage (Melo, 2004;Baggenstoss et al, 2008), and significant changes to coffee's physical properties have been observed to occur during roasting (Mwithiga & Jindal, 2003). Grinding results in powdery products that can have different particle sizes according to the market's needs (Schmidt et al, 2008) and affect the physical properties of coffee (Geldart et al, 2009;Langroudi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, green beans with a high moisture content will exhibit a greater dehydration rate and a faster increase in RL than drier beans, while organic roast loss (ORL: defined as the percent loss of organic dry matter) may be only slightly affected. 5,48 Fast roasting generally produces coffee with a lower density due to the larger volume. As an approximation, a 7.0% of ORL is equivalent to medium roast degree.…”
Section: Moisture Content Roast Loss and Densitymentioning
confidence: 99%
“…Roasting is an essential step in the production of high-quality instant coffee, because this process produces the desired aroma and taste of the beans (Farah et al ., 2006;Mwithiga et al ., 2003). During the roasting process, physical, chemical, structural and sensorial changes in the coffee beans are induced by pyrolysis at temperatures of between 160 ° C and 260 ° C for different periods of time (Hern á ndez et al ., 2007;Pittia et al ., 2001).…”
Section: Roastingmentioning
confidence: 94%